Hospitals and Pharmacy Relationship between Rating, Service Time and Closeness in the City of Skopje - Bozinovski, F.; Simikj, E.; Naumoski, A. (IEEE, 2021)
Due to the urgent global health situation, the hospitals as well as the pharmacy stores are under pressure. Therefore, the aim of our project is to use the geo-spatial information of these two objects in Skopje, the capital of North Macedonia, and to represent their detail information to find the closest pharmacy near the hospital, rate the hospitals and pharmacies based on user customers experience, and provide this information to customers to make online ordering and pick up the order later. To do this, we have collected the data about the hospitals and pharmacy objects, then we import this data in ArcGIS software, and we produce distance, interpolation, and service maps from the data analysis. As results, the final visual representation from our analysis shows possible improvements and possible new locations for pharmacy stores.